Determinants of Rural Women’s Participation in Agricultural Extension Services: Case of Irrigable Vegetable Production in Oromia Region, Ethiopia - Sitachew, Mulutena; Jeyabalasingh, Paul Mansingh; Debela, Mulu (Journal of Extension Education, 2019)
Women rarely participate in extension services and have little contact with extension service organizations. Increasing extension service to female farmers in rural areas of Ethiopia remains challenging. Reports say that there is low participation of women vegetable farmers in agricultural extension services in Toke-Kutayedistrict, Oromia region, Ethiopia.Therefore, this study seeks to assess the factors influencing rural women participation in agricultural extension services employing both qualitative and quantitative approaches. Out of the 132 women vegetable producers selected for this study, there were 79 participants and 53 non-participants of agricultural extension services. Quantitative data from primary sources were collected using a semi-structured interview schedule. Qualitative data were collected through key informant interviews and focus group discussions.The results of the Binary Logit regression model estimate indicate that out of the 16 explanatory variables included in the model, farming experience, sex of development agent, irrigable land holding size and access to credit shows significant and positive relation with participation whereas, time spent on domestic activities, distance from water source, mobility constraints and sex of household headship shows significant and negative relationship with women participation.